In-fiber Mach–Zehnder interferometer based on polarization-maintaining fiber for displacement and temperature sensing - Cheng, Jun-ni; Jiang, Xiao-yan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
A displacement sensor based on polarization-maintaining fiber has been proposed and proved in experiment. The polarization-maintaining fiber (PMF) is sandwiched with two graded-index multimode fibers (GI MMF), which form the Mach–Zehnder interferometer (MZI) sensor. Graded-index multimode fiber serve as an optical coupler for modes conversion. The results show that with the increase of displacement, the spectrum moves to the long wavelength direction, but when temperature increases, the spectrum has a red shift, which means that the displacement and temperature can be measured separately according to the wavelength drift direction. The sensor consists of 4 mm GI MMF and 14 mm PMF, which can exhibit the displacement sensitivity of –9.275 pm/μm in the range of 0–600 μm. In addition, temperature will also affect the sensitivity of displacement measurement, so the sensitivity of the sensor to temperature is also measured. The results show that the selected monitoring dip provides a better temperature sensitivity of 33.605 pm/℃ in the range of 35–75℃. The sensor is easy to fabricate and does not has any functional coating, which make it become a good candidate in the industrial field.
Optica Applicata, Vol. 53, 2023, nr 1, s. 21-33
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; displacement sensing; polarization-maintaining fiber (PMF); graded-index multimode fiber; Mach–Zehnder interferometer